1974
DOI: 10.1021/ja00819a043
|View full text |Cite
|
Sign up to set email alerts
|

Proton transfer mass spectrometry of peptides. Rapid heating technique for underivatized peptides containing arginine

Abstract: Consideration of the kinetics of the evaporation of peptides leads to two approaches to volatility enhancement. An obvious direction to take is to attempt to reduce the energy of bonding of molecules to surfaces by dispersal onto surfaces which are relatively inert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
3

Year Published

1976
1976
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(100 citation statements)
references
References 1 publication
4
93
0
3
Order By: Relevance
“…Other major ions also re ect the fundamental backbone structure of the polymer. 3) Minor secondary thermal decomposition observed with lament temperature even above 500°C is the useful gure of merit for the present technique, verifying the concept given by Beuhler et al 2) It should be noted that the less-volatility compounds dealt with desorbed at rather low lament temperatures (e.g., 154°C). 3) is suggests that there might be some tribological e ect in addition to the thermal e ect in the desorption process of less-volatility compounds.…”
Section: Flash Surface Heating/rapid Coolingsupporting
confidence: 85%
See 1 more Smart Citation
“…Other major ions also re ect the fundamental backbone structure of the polymer. 3) Minor secondary thermal decomposition observed with lament temperature even above 500°C is the useful gure of merit for the present technique, verifying the concept given by Beuhler et al 2) It should be noted that the less-volatility compounds dealt with desorbed at rather low lament temperatures (e.g., 154°C). 3) is suggests that there might be some tribological e ect in addition to the thermal e ect in the desorption process of less-volatility compounds.…”
Section: Flash Surface Heating/rapid Coolingsupporting
confidence: 85%
“…2) ey found that thermal desorption becomes more favorable than thermal decomposition at higher temperature for some peptides even when the activation energy of desorption is larger than the bond dissociation energy. is phenomenon was interpreted based on the "classic" Arrhenius reaction rate theory for thermal desorption and decomposition.…”
Section: Thermal Vs Non-thermal Desorptionmentioning
confidence: 99%
“…Also, this low absorptivity means that when dealing with a relatively thick layer of organic material, the temperature distribution at the surface and in the bulk will be important. The absorption coefficient, therefore, affects the rate of Early studies on the evaporation of thermolabile molecules from rapidly heated wires suggested that normally thermolabile molecules could be desorbed if heated rapidly enough [31]. This effect could be explained in terms of the activation energies of the evaporation and pyrolysis reactions.…”
Section: Discussionmentioning
confidence: 99%
“…In the thermal mechanism, the surface nanostructures provide a thermal conduction barrier that tends to trap absorbed laser energy momentarily in the nano-dimension. It thus causes a rapid surface heating, which may promote intact desorption of thermally labile molecules [12,13]. On the other hand, nonthermal contributions to the desorption process have also been proposed.…”
Section: Introductionmentioning
confidence: 99%